2015
DOI: 10.1128/aem.02446-14
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Human-Specific Bacteroidales and Fecal Indicator Bacteria in an Urban Watershed Impacted by Sewage Pollution, Determined Using RNA- and DNA-Based Quantitative PCR Assays

Abstract: The identification of fecal pollution sources is commonly carried out using DNA-based methods. However, there is evidence that DNA can be associated with dead cells or present as "naked DNA" in the environment. Furthermore, it has been shown that rRNA-targeted reverse transcription-quantitative PCR (RT-qPCR) assays can be more sensitive than rRNA gene-based qPCR assays since metabolically active cells usually contain higher numbers of ribosomes than quiescent cells. To this end, we compared the detection frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 54 publications
(80 reference statements)
3
49
0
Order By: Relevance
“…; Kapoor et al . ). Our results indicated that active bacterial communities analysed as rRNA transcript libraries were different than that observed in the corresponding rDNA libraries in the circulating hot water biofilm ( Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Kapoor et al . ). Our results indicated that active bacterial communities analysed as rRNA transcript libraries were different than that observed in the corresponding rDNA libraries in the circulating hot water biofilm ( Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 97%
“…; Kapoor et al . ). Recently, rRNA transcripts have been used as templates in NGS studies (Jalava et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Kapoor et al . ; Inkinen et al . ) as they provide information on the active fraction of microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…; Kapoor et al . ). Furthermore, bioelectronalytical systems are inherently scalable, a property which has been extensively discussed in the literature in the context of microbial fuel cells (Logan, ,b).…”
Section: Introductionmentioning
confidence: 97%